An Evidence‐Based Rationale for Adopting Weight‐Inclusive Health Policy. Issue 1 (16th January 2020) - Hunger, Jeffrey M.; Smith, Joslyn P.; Tomiyama, A. Janet
Abstract: Health policies routinely emphasize weight loss as a target for health promotion. These policies rest upon the assumptions: (1) that higher body weight equals poorer health, (2) that long‐term weight loss is widely achievable, and (3) that weight loss results in consistent improvements in physical health. Our review of the literature suggests that these three assumptions underlying the current weight‐focused approach are not supported empirically. Complicating this further are the misguided assumptions (4) that weight stigma (i.e., pervasive social devaluation and denigration of higher weight individuals) promotes weight loss and (5) recognizing that one is "overweight" is necessary to spur health‐promoting behaviors. We highlight throughout how these assumptions have manifested in current policies and offer suggestions for alternative approaches to health promotion. We conclude by advocating for the broad adoption of a weight‐inclusive approach to health policy. Abstract :